Analysis of Structure, Conduct and Performance of Fashion Industry in Indonesia - Nabila, Destiati; Firmansyah, Firmansyah (Efficient: Indonesian Journal of Development Economics, 2021)
The fashion industry has a good contribution to the Indonesian economy. The Indonesian government responded to this potential by setting a strategic plan to become the center of world muslim fashion. This plan can be achieved by improving the performance of fashion industry. In the SCP paradigm, the performance of an industry is influenced by its market structure and its behavior. The results of regression using the fixed effect model (FEM) show that market share and PMA ratios have a significant and negative effect on PCM variable. The internal efficiency variable has a significant and positive effect on PCM variable. While the productivity variable does not have a significant effect on PCM variable. Industri fashion memiliki kontribusi yang baik bagi perekonomian Indonesia. Potensi tersebut direspons oleh Pemerintah Indonesia dengan menyusun rencana strategis untuk menjadi pusat fashion muslim dunia. Rencana ini dapat dicapai dengan meningkatkan kinerja industri fashion. Dalam paradigma SCP, kinerja suatu industri dipengaruhi oleh struktur pasar dan perilakunya. Hasil regresi dengan menggunakan model fixed effect (FEM) menunjukkan bahwa pangsa pasar dan rasio PMA berpengaruh signifikan dan negatif terhadap variabel PCM. Variabel efisiensi internal berpengaruh signifikan dan positif terhadap variabel PCM. Sedangkan variabel produktivitas tidak berpengaruh signifikan terhadap variabel PCM.